Homogeneous Liquid-Liquid Extraction Method for Selective Separation and Preconcentration of Trace Amounts of Palladium - Mohammad Reza Jamali; Yaghoub Assadi; Reyhaneh Rahnama Kozani; Farzaneh Shemirani (E-Journal of Chemistry)
A simple and effective homogeneous liquid-liquid extraction method for selective separation, preconcentration and spectrophotometric determination of palladium(II) ion was developed by using a ternary component system (water / tetrabutylammonium ion (TBA+) / chloroform). The phase separation phenomenon occurred by an ion–pair formation of TBA+ and perchlorate ion. Thio-Michler’s ketone (TMK), 4, 4ˊ-bis (dimethylamino) thiobenzophenone, was used as a complexing agent. After optimization of complexation and extraction conditions ([TMK]=5.0x10-2 mol L-1, [TBA+] = 2.0×10-2 mol L-1, [CHCl3] = 60.0 µL, [ClO4-] = 2.5×10-2 mol L-1 and pH= 3.0), a preconcentration factor 10 was obtained for 10 mL of sample. The analytical curve was linear in the range of 2-100 ng mL-1 and the limit of detection was 0.4 ng mL-1. The relative standard deviation was 3.2% (n=10). Accuracy and application of the method was estimated by using test samples of natural and synthetic water spiked with different amounts of palladium(II) ion. The method is very simple and inexpensive.